teatro a escena o técnicas de expresión oral y escrita - García de Rivera Hurtado, Marian (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2001)
This experience explores theatrical performance inside the Spanish Educational System. It gives special relevance to the different levels in programming and to the steps needed to take the theatrical activities from the normative curriculum to the daily practice in the educational centers and in the classroom. The author shows the reality of education and proposes some working tools to state explicitly those drama activities in the curriculum.